(untitled) (Alternautas, 2022)
Despite its historic roots, the Social Solidarity Economy (SSE) is a concept that has come to prominence in South America over the last decade. It is an alternative theoretical construct of “the economy” that seeks to emphasise relationships of solidarity in an attempt to reinstate the primacy of “society” over “the market”. What makes the SSE distinctive is that while it (mostly) professes itself to be a theoretical construct, it is also explicitly intended to be a guide for policy. This contribution first examines the SSE as an intellectual construct, noting the lack of consistency around the term. It then proceeds to relate these conceptions to the practice of the SSE in the field, looking at the program Mobiliario Escolar, introduced by the Ecuadorian government in 2014. There, the SSE shows much potential, with its slightly ambiguous definition lending it a certain utility for guiding policy. Most importantly, the SSE is shown to be a beneficial example of practice-oriented theory.